2022
DOI: 10.1088/2515-7620/aca9ad
|View full text |Cite
|
Sign up to set email alerts
|

Electricity access in Uganda’s slums: multi-stakeholder perspectives from Kampala

Abstract: Uganda’s rapid urbanisation poses service delivery challenges, particularly to the poorest neighbourhoods which are home to over half of the urban population. Only 63% of urban households have access to grid-electricity, and access deficits are most felt in slums despite their proximity to the grid. This study investigated the electricity access challenge in Uganda’s slums and the socio-political issues that shape access, from the perspective of multiple stakeholders. Using mixed methods, eight semi-structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…It was observed that about 23% of Uganda's population has access to electricity of which 7% of the population comes from the rural area [48] [49]. Energy has seriously taken another evolutional step to impact the lives of the citizens by countries adopting and implementing energy policies in their various capacities [51].…”
Section: Finding and Discussionmentioning
confidence: 99%
“…It was observed that about 23% of Uganda's population has access to electricity of which 7% of the population comes from the rural area [48] [49]. Energy has seriously taken another evolutional step to impact the lives of the citizens by countries adopting and implementing energy policies in their various capacities [51].…”
Section: Finding and Discussionmentioning
confidence: 99%
“…The informal settlements included Kinawataka; Luzira; Luzira-Kirombe; Kitintale, Nalukolongo; Wankulukuku-Kabowa; Kamwokya; Bwaise; Wandegeya; Katwe-Kinyoro; Namuwongo-Soweto and Kyebando.The geographical representation of the entire city was considered while selecting each of these informal settlements. Kampala’s informal settlements are characterised by high levels of psychoactive substance use, poverty and unemployment [ 41 – 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…The theme on "energy for agriculture", meanwhile, examines issues such as the role of energy access in facilitating access to groundwater for irrigation, the influence of different electricity pricing mechanisms on groundwater conservation, and the impact of tubewell irrigation on crop production (Bhandari, 2001;Evans et al, 2012;Sidhu et al, 2020). The lack of access to amenities (including electricity) in urban slums-often despite their proximity to the electricity grid-are highlighted in the theme on "slum electrification" (van Leeuwen et al, 2017;Yaguma et al, 2022). Finally, the theme on "energy governance" addresses issues such as the lack of local level capacity for the devolution of energy governance, the role of energy communities in energy governance, and the influence of politics on electricity access reform in low-and middle-income countries (Gore et al, 2019;Gebreslassie et al, 2022;Volkert and Klagge, 2022).…”
Section: Themes In the Policy-related Research On Energy Accessmentioning
confidence: 99%